Pembaharuan Sistem Pendidikan Seksualitas di Pesantren - Nurul Khasanah; Kurnia Intan Nabila (UPT Pusat Studi Aswaja UNISNU Jepara, 2023)
AbstactSexuality education in Islamic boarding schools has an important role in shaping the social life of adolescents and protecting them from the risk of sexual violence. However, with the times and increasingly complex needs, there is an urgent need to update the sex education system in Islamic boarding schools. This study aims to identify the implications of reforming the sex education system in Islamic boarding schools. This research involves an analysis of literature and sources relevant to sex education in Islamic boarding schools. The results of the analysis show that reforming the sex education system in Islamic boarding schools is very important to address the challenges faced by adolescents in the context of sexuality. The implication of this research is the need for collaboration between Islamic boarding schools, the government, and the community in updating the approaches and methods of teaching sex education. Policymakers and educators in Islamic boarding schools need to realize the importance of updating the approaches and methods used in sex education, and recognizing that sexuality education is not something that is taboo or ignored. In addition, the implications of this research also highlight the importance of empowering parents and the Islamic boarding school community in supporting sex education. Parents need to be given sufficient understanding and skills to provide sexual education to their children, while the pesantren community can be a place for students to obtain correct information and counseling regarding sexuality. Â Keywords: Reformation, Sex Education, Pesantren.Â AbstrakPendidikan seksualitas di pesantren memiliki peran penting dalam membentuk kehidupan sosial remaja dan melindungi mereka dari risiko kekerasan seksual. Namun, dengan perkembangan zaman dan kebutuhan yang semakin kompleks, terdapat kebutuhan yang mendesak untuk memperbarui sistem pendidikan seksualitas di pesantren. Penelitian ini bertujuan untuk mengidentifikasi implikasi dari pembaharuan sistem pendidikan seksualitas di pesantren. Penelitian ini melibatkan analisis terhadap literatur dan sumber-sumber yang relevan dengan pendidikan seksualitas di pesantren. Hasil analisis menunjukkan bahwa pembaharuan sistem pendidikan seksualitas di pesantren sangat penting untuk menjawab tantangan yang dihadapi oleh remaja dalam konteks seksualitas. Implikasi dari penelitian ini adalah perlunya kolaborasi antara pesantren, pemerintah, dan masyarakat dalam memperbarui pendekatan dan metode pengajaran pendidikan seksualitas. Para pengambil kebijakan dan pendidik di pesantren perlu menyadari pentingnya memperbarui pendekatan dan metode yang digunakan dalam pendidikan seksualitas, serta mengakui bahwa pendidikan seksualitas bukanlah sesuatu yang tabu atau diabaikan. Selain itu, implikasi penelitian ini juga menyoroti pentingnya pemberdayaan orang tua dan komunitas pesantren dalam mendukung pendidikan seksualitas. Orang tua perlu diberi pemahaman dan keterampilan yang cukup untuk memberikan pendidikan seksualitas kepada anak-anak mereka, sedangkan komunitas pesantren dapat menjadi tempat bagi santri untuk memperoleh informasi dan konseling yang benar mengenai seksualitas. Â Kata Kunci: Pembaharuan, Pendidikan Seksualitas, Pesantren.